2019
DOI: 10.1111/ppa.12993
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic species and population genetic structure of Plasmopara viticola in São Paulo State, Brazil

Abstract: Downy mildew (Plasmopara viticola) is one of the most important diseases in grape-growing areas worldwide, including Brazil. To examine pathogen population biology and structure, P. viticola was sampled during the 2015/16 growing season from 516 lesions on nine grape cultivars in 11 locations in subtropical areas of São Paulo State, Brazil. For identification of cryptic species, a subsample of 130 isolates was subjected to cleaved amplified polymorphic sequence (CAPS) analysis, and for 91 of these isolates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…For instance, lower clonal fraction (0.04) and higher genotypic diversity (G = 40.69) were observed in Rio Grande do Sul compared to São Paulo (clonal fraction = 0.81; G = 2.98). A recent study also revealed that P. viticola populations from São Paulo had low genetic diversity, where 19 of the 55 MLGs were clonal and represented 93% of the isolates sampled (Camargo et al, 2019). Meanwhile, the high diversity observed in Rio Grande do Sul is similar to that in Europe, where sexual reproduction appears to play a major role in downy mildew epidemics (Gobbin et al, 2006;Delmas et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For instance, lower clonal fraction (0.04) and higher genotypic diversity (G = 40.69) were observed in Rio Grande do Sul compared to São Paulo (clonal fraction = 0.81; G = 2.98). A recent study also revealed that P. viticola populations from São Paulo had low genetic diversity, where 19 of the 55 MLGs were clonal and represented 93% of the isolates sampled (Camargo et al, 2019). Meanwhile, the high diversity observed in Rio Grande do Sul is similar to that in Europe, where sexual reproduction appears to play a major role in downy mildew epidemics (Gobbin et al, 2006;Delmas et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, the climate in São Paulo is favorable all year-round for grapevine growth and green tissues are present during almost the entire year due to the double pruning system commonly used in the state. Thus, P. viticola reproduces and survives predominantly asexually on green tissues (Camargo et al, 2019). Due to the mild winter in South Africa, P. viticola populations often experience bottlenecks at the end of the growing season and a few highly adapted genotypes can survive between seasons as asexual spores or as vegetative mycelium (Koopman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…viticola is <20 m per secondary disease cycle (Gobbin et al ., 2005). However, population genetic structure studies have demonstrated that identical multilocus genotypes can be observed at distant locations, indicating that long‐distance dispersal may be possible (Camargo et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Advances in P. viticola -omics (14)(15)(16)(17)(18)(19) and population genetic studies (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) have improved our knowledge of the grapevine downy mildew pathosystem. In its native range, five cryptic species (also called formae speciales) have recently been identified in the P. viticola species complex, with genetic differentiation and contrasting host ranges on various Vitis and related species (33,34).…”
Section: Introductionmentioning
confidence: 99%